Bortezomib plus dexamethasone induction followed by autologous stem cell transplantation in multiple myeloma: A study from India - Kumar, Jeevan; Minhas, Sachin; Khillan, Kamini; Bhargava, Manorama; Aggarwal, Shyam (Asian Journal of Medical Sciences, 2016)
Background: The use of novel agents for induction prior to autologous stem cell transplantation (ASCT) has considerably improved the complete response (CR) rate in multiple myeloma (MM) patients. There are very few studies from the developing countries on the use of novel agents followed by ASCT. Aims and Objectives: The current study was aimed for retrospective evaluation of the efficacy and response rates of induction with bortezomib (Velcade) plus dexamethasone (VD regimen) followed by ASCT in Indian patients. Materials and Methods: Ten patients with newly diagnosed, symptomatic MM who had received four cycles of VD induction before stem cell collection were evaluated. High dose melphalan was given for conditioning followed by stem cell transfusion. Thalidomide or lenalidomide was used as post-transplantation maintenance treatment. Results: Post VD induction, the overall response rate (ORR) was 90% including 20% CR, 40% very good partial response (VGPR), and 30% partial response (PR). Post ASCT, the ORR was 100%, including 80% CR and 20% VGPR. The 5-year overall survival and progression free survival rates were 65.6% and 57.1%, respectively. Conclusions: The VD induction regimen was effective and well tolerated in this retrospective analysis of Indian patients with newly diagnosed MM. It significantly improved the post-induction and post-transplant response rates without affecting stem cell collection. Asian Journal of Medical Sciences Vol.7(4) 2016 44-48